The genus Parabaliothrips Priesner (Thysanoptera, Thripidae) with three new species from Japan and Taiwan, and two new records of related genera from Japan - Masumoto, Masami; Okajima, Shûji (Zootaxa, 2020)
A new diagnosis of the genus Parabaliothrips is provided, together with a key to the nine recognized species and descriptions of the following: P. betulaceae n.sp., P. brevisetosus n.sp. and P. robustus n.sp. The European species Firmothrips firmus and Iridothrips mariae are newly recorded from Japan.